Analisis Faktor yang Mempengaruhi Minat Gen Z dalam Berinvestasi di Pasar Modal (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis di Solo Raya) - Ardi Bagus S; Siti Aisyah (Ekonomis: Journal of Economics and Business, 2023)
The readiness of the younger generation to tackle financial challenges is a crucial thing that must be taken into account in order to maintain a good living standard in the future.The right saving method is an important aspect of managing and achieving financial targets, one of which is in the form of investment in the capital market. The younger generation is a potential target for the financial (investment) industry sector because they have sufficient knowledge of investment products and have a long saving period before reaching unproductive age. There are several factors that can encourage the younger generation to invest in the capital market. This study aims to analyze the factors of investment knowledge, investment benefits, financial literacy and return expectations which can affect one's investment interest, especially the younger generation such as university students. This study uses primary data by distributing questionnaires to respondents, and nalyzeda using linear regression with the SPSS 25 software. The results of the study indicate that investment knowledge and expected return influences investment interest, especially among students who are currently studying in the Solo Raya area.The government and related institutions need to increase the participation of young people in various investment alternatives, so as to increase national development funding sources.